2013
DOI: 10.1111/jonm.12067
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical gains of nurse-led medication monitoring profiles

Abstract: The West Wales Adverse Drug Reaction profile offers opportunities to improve care. Medication monitoring provides the structure to concurrently monitor known adverse drug reactions. Practice-based adverse drug reaction profiles benefit from cognitive, content validity and inter-rater reliability testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 117 publications
(179 reference statements)
2
16
0
Order By: Relevance
“…Further, the implementation of proactive medication monitoring in clinical practice, such as the West Wales Adverse Drug Reaction Profile, could be an important approach in identifying the potential ADRs associated with commonly prescribed medications (Jordan et al . , Gabe & Jordan , Gabe et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the implementation of proactive medication monitoring in clinical practice, such as the West Wales Adverse Drug Reaction Profile, could be an important approach in identifying the potential ADRs associated with commonly prescribed medications (Jordan et al . , Gabe & Jordan , Gabe et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…No educational programme is effective without organisational change and vice versa. To succeed, the implementation of proactive medication monitoring, such as nurse‐led ADR profiles (Gabe & Jordan ), needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…). Fostering organisational empowerment towards ADR reporting should improve proactive medication monitoring in clinical practice, such as in the West Wales Adverse Drug Reaction Profile (Gabe & Jordan ). In fact, several recent studies have shown better quality and safer medication monitoring using the West Wales Adverse Drug Reaction Profile for patients with dementia in a nursing home (Jordan et al .…”
Section: Discussionmentioning
confidence: 99%
“…A mixed‐methods design was used for development, validation and reliability testing of the prototype Cape Town MEWS‐linked SBAR tool (Gabe & Jordan, ; Grove, Burns, & Gray, ). In research, epistemological and methodological pluralism is aimed at producing more effective research (Johnson & Onwuegbuzie, ).…”
Section: Methodsmentioning
confidence: 99%
“…In research, epistemological and methodological pluralism is aimed at producing more effective research (Johnson & Onwuegbuzie, ). To identify potential measurement or response error, we undertook CIs to explore the interpretation of the SBAR tool by future users (nurses and medical doctors), content validity analysis (Lynn, ; Yaghmale, ) and IRR testing (Gabe & Jordan, ).…”
Section: Methodsmentioning
confidence: 99%